KONSEP MODAL KEROHANIAN MENURUT PERSPEKTIF EKONOMI ISLAM: The Concept of Spiritual Capital from Islamic Economic Perspective - Wahid, Hairunnizam; Nik Ab Malik, Nik Mohd Azim; Ismail, Mohd Adib (Jurnal Syariah, 2023)
Spiritual capital is essential for promoting the quality of economic growth. Spiritual capital is a multidimensional and flexible concept. Consequently, the concept has been discussed in numerous social science and humanities disciplines, such as theology, economics, sociology, etc. The discussion has produced numerous definitions of the concept of spiritual capital. Therefore, the purpose of this study is to examine the concept of spiritual capital from an Islamic economics perspective. Qualitative methode has been used in this research where relevant literatures have been critically reviewed. Spiritual capital, according to Islamic economics, is an intangible asset in the form of a source of inner strength that is fueled by the accumulation of religious knowledge and spiritual practices based on both obligatory and supererogatory worships in Islam, which can have a positive impact on those who invest in it.